Small molecule inhibitors of receptor tyrosine kinases - Krause, Daniela (Henry Stewart Talks, 2009)
Overview of tyrosine kinases, Tyrosine kinase dysregulation in cancer, The example of chronic myelogenous leukemia, Receptor tyrosine kinases: function and involvement in cancer, treatment with small molecule inhibitors to these tyrosine kinases, Inhibition of several tyrosine kinases, Toxicity, Resistance, The future of treatment with tyrosine kinase inhibitors
Reviewed at 2022/04/12